2012
DOI: 10.1002/mawe.201200007
|View full text |Cite
|
Sign up to set email alerts
|

Material properties and formability of extruded Al‐Mg compounds as a function of temperature

Abstract: Die ersten Untersuchungen der hydrostatisch stranggepressten Al‐Mg Verbunde als Halbzeuge für Folgeprozesse wie Gesenkschmieden verdeutlichen das große Potenzial hybrider Werkstoffverbunde. Die experimentellen Analysen ergaben, dass die Grenzschicht ein hohes Umformvermögen aufweist. Mit verschiedenen Gesenkschmiedeoperationen konnten Umformgrade von 1,50 erreicht werden, ohne dass eine Schädigung in der Grenzschicht auftrat. Die numerischen Untersuchungen ergaben keine signifikanten Dehnungsunterschiede in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…Macro and microscopic analyzes demonstrated that the final pieces did not present cracks or specific surface damage. This outcome aligns with those of FEUERHACK et al (2013), who investigated the axial and radial strain of Al-Mg bimetallic core bosses[23].The forming parameters did not lead to a metallurgical bond between the metals composing the bimetallic crosshead. However, the forged component exhibits rotational and axial interlocking due to metal flow.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Macro and microscopic analyzes demonstrated that the final pieces did not present cracks or specific surface damage. This outcome aligns with those of FEUERHACK et al (2013), who investigated the axial and radial strain of Al-Mg bimetallic core bosses[23].The forming parameters did not lead to a metallurgical bond between the metals composing the bimetallic crosshead. However, the forged component exhibits rotational and axial interlocking due to metal flow.…”
supporting
confidence: 90%
“…Next, mesh convergence was performed to refine the selection of mesh parameters. 2013), who investigated the axial and radial strain of Al-Mg bimetallic core bosses [23].…”
Section: Methodsmentioning
confidence: 99%
“…The subproject B3 analyzes the production of Al-Mg compounds (AlMgSi1/AZ31) with the primary focus on the interface properties and the characterization of such kinds of compounds. Previous publications described the production process, the optimization steps for establishing flawless and completely bonded compounds as well as the simulation models for the numerical analyses and the prediction of the compound quality [2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the use of DIC and a polynomial, such a point of discontinuity is not detectable in the presented investigation. However, smoothing does not change the sign, and because both materials exhibit similar stress strain curves at 300 °C , the dimension of the hrr values is detected correctly. Therefore, the coefficient values of hrr could be considered as uncritical because of the moderate interface strength .…”
Section: Resultsmentioning
confidence: 97%